Double-carbon-coated SiOx material as well as preparation method and application thereof
By using the CVD method on SiOx material to achieve dual carbon coating, a double carbon coating structure of one-dimensional carbon and amorphous carbon is generated, which solves the problems of poor conductivity and volume expansion of SiOx material, and significantly improves the electrochemistry of lithium-ion batteries. performance.
Patent Information
- Application Number
- CN202411646326.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
AI Technical Summary
The poor conductivity and volume expansion problems of SiOx anode materials in lithium-ion batteries limit their application potential.
The preparation of dual-carbon coated SiOx material was achieved at low and high temperatures by chemical vapor deposition (CVD) method, and a double-carbon coated structure of one-dimensional carbon and amorphous carbon was generated by transition metal catalysis.
It significantly improves the first-circle Coulomb efficiency and cycle stability of lithium-ion batteries, improves the conductivity of SiOx material, and effectively buffers volume expansion.
Smart Images

Figure CN119481000A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and particularly relates to SiO x negative electrode material. Background Art
[0002] In recent years, with the rapid development of electric vehicles and hybrid vehicles, people's demand for lithium-ion batteries with high energy density has been increasing. Among the many candidate materials, silicon oxide materials (SiO x ) has attracted much attention due to its excellent cycle stability and high specific capacity. However, SiO x The poor conductivity and volume expansion (about 200%) of SiO2 limit its potential in practical applications. To solve these problems, researchers proposed to synthesize SiO2 with different structures. x Generally, amorphous carbon can form a dense carbon layer due to its isotropic structure to buffer the volume expansion during lithiation, but its electronic conductivity is not ideal. In contrast, one-dimensional carbon materials such as carbon nanotubes (CNTs) or carbon nanofibers (CNFs) are also used to combine with SiO due to their high electrical conductivity. x However, one-dimensional carbon materials have problems in practical applications such as difficulty in structural control and poor uniformity, which may lead to material agglomeration, thus limiting the improvement of composite material performance.
[0003] Ideal SiO x The carbon / carbon composite structure should be multifunctional, and the carbon component should play a dual protective role, both mitigating volume changes and improving electrical conductivity. Traditionally used carbon sources are mostly carbon-containing compounds, which can often only synthesize a single carbon layer. Chemical vapor deposition (CVD) using carbon source gases has advantages over conventional carbon / carbon composites: (1) the growth process can be finely controlled by precisely controlling the gas flow rate and reaction conditions; (2) the CVD process is relatively easy to scale up and is suitable for industrial-scale production; and (3) using gases as carbon sources can reduce byproducts and pollution during the reaction. For example, patent publication number CN 113363479 A discloses a double-layer carbon-coated silicon oxide negative electrode material, its preparation method and application, wherein the silicon oxide negative electrode material includes silicon oxide material, a first carbon coating layer and a second carbon coating layer from the inside to the outside; the first carbon coating layer is formed by liquid phase coating or solid phase melting coating, the second carbon coating layer is formed by gas phase coating, or the first carbon coating layer and the second carbon coating layer are respectively formed by gas phase coating of different types of gas phase carbon sources; the gas phase carbon source is a saturated hydrocarbon or an unsaturated hydrocarbon. This patent uses two layers of carbon materials with different structures to coat silicon oxide, and through the mutual cooperation and synergistic effect between the two layers of carbon coating layers, it can effectively improve the cycle performance of the battery. However, this patent does not improve the SiO x The conductivity of the negative electrode material, SiOx The electrochemical performance of C / C composites still has room for improvement. Summary of the Invention
[0004] Aiming at the technical problems of poor conductivity and easily damaged structure of silicon-based materials of batteries, the present invention proposes a double carbon-coated SiO x The material, its preparation method and application, realize the double carbon layer structure of silicon-oxygen material through the carbon production mechanism of CVD carbon source gas, that is, the combination of low-temperature catalytic growth and high-temperature pyrolysis deposition, thereby improving the first-cycle coulombic efficiency of the battery and the cycle stability of the battery.
[0005] In order to achieve the above object, the technical solution of the present invention is achieved as follows:
[0006] A double carbon-coated SiO x The method for preparing the material comprises the following steps:
[0007] (1) mixing silicon oxide and a transition metal source and grinding them to obtain a mixture;
[0008] (2) subjecting the mixture to low-temperature chemical vapor deposition to achieve carbon coating to obtain a one-dimensional carbon-coated silicon-oxygen material;
[0009] (3) The one-dimensional carbon-coated silicon oxide material is subjected to high-temperature chemical vapor deposition to achieve secondary carbon coating to obtain double carbon-coated SiO x Material.
[0010] The particle size of the silicon oxide is 13-48 μm, SiO x If the particles are uneven, the carbon coating effect will be poor.
[0011] The transition metal source is ammonium oxalate iron salt, nickel nitrate, cobalt nitrate, and indium nitrate.
[0012] The mass ratio of the silicon oxide to the transition metal source is 1:(10-50).
[0013] The atmosphere of the low-temperature chemical vapor deposition and high-temperature chemical vapor deposition in the heating stage is an inert gas, and in the heat preservation stage is a mixed gas of the inert gas and the carbon source gas.
[0014] The inert gas is argon or nitrogen; the carbon source gas is acetylene, methane, or toluene; and the volume flow ratio of the inert gas to the carbon source gas in the mixed gas is 1-10:1.
[0015] The temperature of the holding stage in the low-temperature chemical vapor deposition is 400-700°C and the holding time is 5-30 minutes. If the carbon deposition temperature is too low and the holding time is too short, only a small amount of one-dimensional carbon (C1) will grow on the SiO xThe surface of the particles is relatively smooth; the low-temperature carbon deposition temperature is too high, resulting in the destruction of the three-dimensional conductive network composed of one-dimensional carbon (C1).
[0016] The temperature of the holding stage in the high temperature chemical vapor deposition is 700-900°C and the time is 5-30 minutes. If the high temperature carbon deposition temperature is too low, only a small amount of amorphous carbon (C2) will be deposited on the SiO x On the particle surface, the amorphous coating is thin, and the temperature is not enough, resulting in insufficient bonding strength with the particles; the high-temperature carbon deposition temperature is too high, resulting in excessive deposition of amorphous carbon (C2) on the SiO x On the particle surface, the three-dimensional conductive network composed of one-dimensional carbon (C1) is destroyed.
[0017] The above double carbon-coated SiO x Application of materials in lithium batteries, double carbon coated SiO x The material is used as the active material in the electrode sheet. The electrode sheet is made by coating SiO with double carbon. x The material, conductive agent and binder are mixed and then coated on the current collector to make it.
[0018] The mass ratio of the double-carbon-coated silicon oxide material, the conductive agent and the binder is (7-9.3): (0.3-2): (0.4-1); the conductive agent is any one of acetylene black, Ketjen black, conductive graphite or Super P; and the binder is any one of styrene-butadiene rubber, sodium carboxymethyl cellulose or polyacrylic acid.
[0019] Preferably, the binder includes carboxymethyl cellulose, and styrene-butadiene rubber emulsion or polyacrylic acid; the mass ratio of carboxymethyl cellulose to styrene-butadiene rubber emulsion or polyacrylic acid is 2:3.
[0020] In the battery, the above-mentioned electrode sheet is the negative electrode, the lithium sheet is the positive electrode, 500 μL of electrolyte is added to each of the electrode sheet and the lithium sheet, and a separator is provided between the electrode sheet and the lithium sheet; the discharge voltage of the charge and discharge cycle test is 0.01-2V, and the current density is 0.1C-1C.
[0021] Electrolyte for battery assembly: Solute: lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), etc.
[0022] The solvent is carbonate esters such as dimethyl carbonate (DMC), ethylene carbonate (EC), ethyl methyl carbonate (EMC), ethers such as ethylene glycol dimethyl ether (DME)
[0023] Additives: vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0024] Preferably, the electrolyte is LiPF6+ (EC / DEC=1:1, v / v).
[0025] The beneficial effects of the present invention are as follows: by introducing transition metal catalyst into silicon-oxygen material, double carbon coating is achieved at low and high temperature by CVD method, and double carbon coated silicon-oxygen material (SiO x @C1@C2), effectively improving the first-cycle coulombic efficiency and cycle performance of lithium-ion batteries. In this process, conventional solid-phase carbon sources are not used. Instead, carbon source gas is used. Through the carbon production mechanism combining low-temperature catalytic growth of CVD carbon source gas and high-temperature pyrolysis deposition, double carbon coating of one-dimensional carbon and amorphous carbon is achieved. That is, at low temperature, the carbon source gas is cracked under the catalytic action of transition metal to generate one-dimensional carbon, and the generated one-dimensional carbon is entangled with each other under the catalytic action to form a cage-like carbon layer (C1), constructing a three-dimensional conductive network for SiO x The particles provide sufficient contact points and long-range conductive paths throughout the particles, significantly improving the poor conductivity of silicon-oxygen materials. At high temperatures, the carbon source gas pyrolyzes to form amorphous carbon (C2), which is deposited on the SiO x The surface of the material forms a shell-like structure. In addition, combined with the one-dimensional carbon formed at low temperature, it provides a certain compressive stress, which inhibits the SiO x Reacts with lithium to cause a large volume change. At the same time, it effectively prevents SiO x The components are in direct contact with the electrolyte, reducing SiO x By precisely controlling the process temperature and ventilation volume, the side reaction on the SiO x The particle surface is coated with a certain thickness of one-dimensional carbon and deposited amorphous carbon, taking advantage of the high conductivity of one-dimensional carbon and the excellent buffering property of amorphous carbon. These two carbon layers can form a synergistically reinforced double carbon layer structure, effectively buffering the volume expansion of silicon-oxygen materials during the cycle, thereby improving the SiO x During the preparation process, the CVD method allows the carbon source gas to diffuse into the gaps between the particles, and by finely controlling the carbon layer growth process, it prevents the SiO x Direct exposure to the electrolyte further improves the first-cycle Coulombic efficiency and battery cycling stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0027] Figure 1 Silicon oxide SiO x Comparative Example 1: SiO x@C1 and Example 1: SiO x XRD patterns of @C1@C2.
[0028] Figure 2 It is a SEM picture. In the picture, (a) silicon oxide SiO x ; (b) Comparative Example 1: SiO x @C1; (cd) Example 1: SiO x @C1@C2's.
[0029] Figure 3 Comparative Example 2: SiO x TEM images of @C2, a and b are taken at different magnifications.
[0030] Figure 4 (a) Comparative Example 3: SiO x @SEM image of C1; (b) Comparative Example 4: SiO x SEM images of @C1@C2; (c) Comparative Example 4: SiO x TEM images of @C1@C2.
[0031] Figure 5 As raw material silicon oxide SiO x Comparative Example 1: SiO x @C1, Comparative Example 2: SiO x @C2, Example 1: SiO x Comparison of the cycling performance of @C1@C2 materials under the conditions of 0.1C in the first cycle and 0.5C in the subsequent cycle.
[0032] Figure 6 As raw material silicon oxide SiO x Comparative Example 1: SiO x @C1, Comparative Example 2: SiO x @C2, Example 1: SiO x Electrochemical impedance spectroscopy of @C1@C2 materials. DETAILED DESCRIPTION
[0033] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] A double carbon-coated SiO x The material and preparation method include the following steps:
[0036] Step 1: Sieving SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13-48μm. x particles.
[0037] Step 2: Low temperature carbon deposition: Weigh 5 g of sieved SiO x The particles were ground with 0.5g of nickel nitrate in an agate mortar and pestle, then further mixed in a degasser. The mixture was placed in a quartz furnace tube, which was then assembled into a rotary tube furnace and heated to 600°C under an argon atmosphere at a heating rate of 5°C / min and an argon flow rate of 100 sccm. After the temperature reached 600°C, argon (100 sccm) and acetylene (10 sccm) were introduced. Carbon deposition was performed at 600°C for 10 minutes, after which the acetylene flow was stopped.
[0038] Step 3: High-temperature carbon deposition: The above materials were heated from 600°C to 800°C at a heating rate of 3°C / min in an argon atmosphere with an argon flow rate of 100 sccm. After the temperature reached 800°C, argon (100 sccm) and acetylene (10 sccm) were introduced. The temperature was kept at 800°C for 10 minutes for carbon deposition, and then the acetylene gas was stopped. The material was naturally cooled to room temperature in an argon atmosphere to obtain a double-carbon-coated SiO x @C1@C2 composite material.
[0039] Step 4: Prepare electrode sheet: SiO x The @C1@C2 composite material was mixed with a conductive agent (SuperP), a binder (sodium carboxymethyl cellulose (CMC), and a binder (styrene-butadiene latex (SBR)) in a mass ratio of 8:1:0.4:0.6. The mixture was ball-milled to form a slurry. The slurry was evenly coated on copper foil using a coating machine. The electrode sheet was then dried in a vacuum oven at 100°C for 12 hours.
[0040] Step 5: Battery Assembly and Testing: The prepared electrode sheets were assembled into lithium-ion half-cells. Constant-current charge and discharge tests were performed using a Bluetron electrochemical workstation with a test voltage range of 0.01V-2.0V. The resulting material was assembled into a button cell to test its performance as a lithium-ion battery anode material.
[0041] Example 2
[0042] A double carbon-coated SiO x The material and preparation method include the following steps:
[0043] Step 1: Low-temperature carbon deposition: Weigh 5 g of unscreened SiO xThe particles were ground with 0.25g of ammonium oxalate iron salt in an agate mortar and pestle, then further mixed in a degasser. The mixture was placed in a quartz furnace tube, and then assembled into a rotary tube furnace. Under an argon atmosphere, the furnace was heated to 600°C at a rate of 5°C / min, with an argon flow rate of 100 sccm. After the temperature reached 600°C, argon (100 sccm) and acetylene (15 sccm) were introduced. Carbon deposition was carried out by maintaining the temperature at 600°C for 10 minutes, after which the acetylene flow was stopped.
[0044] Step 2: High-temperature carbon deposition: The above materials were heated from 600°C to 800°C at a heating rate of 3°C / min in an argon atmosphere with an argon flow rate of 100 sccm. After the temperature reached 800°C, argon (100 sccm) and acetylene (15 sccm) were introduced. The temperature was kept at 800°C for 10 minutes for carbon deposition, and then the acetylene gas was stopped. The material was naturally cooled to room temperature in an argon atmosphere to obtain a double-carbon-coated SiO x @C1@C2 composite material.
[0045] Example 3
[0046] A double carbon-coated SiO x The material and preparation method include the following steps:
[0047] Step 1: Sieving SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13-48μm. x particles.
[0048] Step 2: Low temperature carbon deposition: Weigh 5 g of sieved SiO x The pellets were ground with 0.3g of cobalt nitrate in an agate mortar and pestle, then further mixed in a degasser. The mixture was placed in a quartz furnace tube, which was then assembled into a rotary tube furnace and heated to 400°C under an argon atmosphere at a heating rate of 10°C / min, with an argon flow rate of 100 sccm. After the temperature reached 400°C, argon (100 sccm) and methane (10 sccm) were introduced. Carbon deposition was performed at 400°C for 5 minutes, after which the methane flow was stopped.
[0049] Step 3: High-temperature carbon deposition: The above materials were heated from 400°C to 800°C at a heating rate of 3°C / min in an argon atmosphere with an argon flow rate of 100 sccm. After the temperature reached 800°C, argon (100 sccm) and methane (10 sccm) were introduced. The temperature was kept at 800°C for 10 minutes for carbon deposition, and then the introduction of methane gas was stopped. The material was naturally cooled to room temperature in an argon atmosphere to obtain a double-carbon-coated SiO x @C1@C2 composite material.
[0050] Example 4
[0051] A double carbon-coated SiO x The material and preparation method include the following steps:
[0052] Step 1: Sieving SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13-48μm. x particles.
[0053] Step 2: Low temperature carbon deposition: Weigh 5 g of sieved SiO x The pellets were ground with 0.5g of indium nitrate in an agate mortar and pestle, then further mixed in a degassing machine. The mixture was placed in a quartz furnace tube, which was then assembled into a rotary tube furnace and heated to 600°C under an argon atmosphere at a heating rate of 5°C / min and an argon flow rate of 100 sccm. After the temperature reached 600°C, argon (100 sccm) and ethylene (10 sccm) were introduced. The carbon deposition was carried out by maintaining the temperature at 600°C for 10 minutes, after which the ethylene flow was stopped.
[0054] Step 3: High-temperature carbon deposition: The above materials were heated from 600°C to 700°C at a heating rate of 5°C / min in an argon atmosphere with an argon flow rate of 100 sccm. After the temperature reached 700°C, argon (100 sccm) and ethylene (10 sccm) were introduced. The temperature was kept at 700°C for 20 minutes for carbon deposition, and then the introduction of ethylene gas was stopped. The material was naturally cooled to room temperature in an argon atmosphere to obtain a double-carbon-coated SiO x @C1@C2 composite material.
[0055] Example 5
[0056] A double carbon-coated SiO x The material and preparation method include the following steps:
[0057] Step 1: Sieving SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13-48μm. x particles.
[0058] Step 2: Low temperature carbon deposition: Weigh 5 g of sieved SiO xThe particles were ground with 0.1g of nickel nitrate in an agate mortar and pestle, then further mixed in a degasser. The mixture was placed in a quartz furnace tube, which was then assembled into a rotary tube furnace and heated to 600°C under an argon atmosphere at a heating rate of 5°C / min and an argon flow rate of 100 sccm. After the temperature reached 600°C, argon (100 sccm) and acetylene (10 sccm) were introduced. Carbon deposition was performed at 600°C for 10 minutes, after which the acetylene flow was stopped.
[0059] Step 3: High-temperature carbon deposition: The above materials were heated from 600°C to 900°C at a heating rate of 3°C / min in an argon atmosphere with an argon flow rate of 100 sccm. After the temperature reached 900°C, argon (100 sccm) and acetylene (10 sccm) were introduced. The temperature was kept at 900°C for 10 minutes for carbon deposition, and then the acetylene gas was stopped. The material was naturally cooled to room temperature in an argon atmosphere to obtain a double carbon-coated SiO x @C1@C2 composite material.
[0060] Example 6
[0061] A double carbon-coated SiO x The material and preparation method include the following steps:
[0062] Step 1: Sieving SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13-48μm. x particles.
[0063] Step 2: Low temperature carbon deposition: Weigh 5 g of sieved SiO x The particles were ground with 0.5g of ammonium oxalate iron salt in an agate mortar and pestle, then further mixed in a degassing machine. The mixture was placed in a quartz furnace tube, and then assembled into a rotary tube furnace. Under an argon atmosphere, the furnace was heated to 700°C at a rate of 10°C / min, with an argon flow rate of 100 sccm. After the temperature reached 700°C, argon (100 sccm) and acetylene (10 sccm) were introduced. The carbon deposition was carried out at 700°C for 30 minutes, after which the acetylene flow was stopped.
[0064] Step 3: High-temperature carbon deposition: The above materials were heated from 600°C to 800°C at a heating rate of 3°C / min in an argon atmosphere with an argon flow rate of 100 sccm. After the temperature reached 800°C, argon (100 sccm) and acetylene (10 sccm) were introduced. The temperature was kept at 800°C for 10 minutes for carbon deposition, and then the acetylene gas was stopped. The material was naturally cooled to room temperature in an argon atmosphere to obtain a double-carbon-coated SiO x @C1@C2 composite material.
[0065] Example 7
[0066] A double carbon-coated SiO x The material and preparation method include the following steps:
[0067] Step 1: Sieving SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13-48μm. x particles.
[0068] Step 2: Low temperature carbon deposition: Weigh 5 g of sieved SiO x The particles were ground with 0.1g of nickel nitrate in an agate mortar and pestle, then further mixed in a degasser. The mixture was placed in a quartz furnace tube, which was then assembled into a rotary tube furnace and heated to 700°C under an argon atmosphere at a rate of 5°C / min, with an argon flow rate of 100 sccm. After reaching 700°C, argon (100 sccm) and methane (50 sccm) were introduced. Carbon deposition was performed at 700°C for 5 minutes, after which the methane flow was stopped.
[0069] Step 3: High-temperature carbon deposition: The above materials were heated from 700°C to 800°C at a heating rate of 3°C / min in an argon atmosphere with an argon flow rate of 100 sccm. After the temperature reached 800°C, argon (100 sccm) and acetylene (50 sccm) were introduced. The temperature was kept at 800°C for 30 minutes for carbon deposition, and then the acetylene gas was stopped. The material was naturally cooled to room temperature in an argon atmosphere to obtain a double-carbon-coated SiO x @C1@C2 composite material.
[0070] Comparative Example 1
[0071] Step 1: Sieving SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13-48μm. x particles.
[0072] Step 2: Low temperature carbon deposition: Weigh 5 g of sieved SiO xThe particles were ground with 0.5 g of nickel nitrate in an agate mortar and then further mixed in a degassing machine. The mixture was placed in a quartz furnace tube, and then a rotary tube atmosphere furnace was assembled and heated to 600 ° C at a heating rate of 5 ° C / min under an argon atmosphere with an argon flow rate of 100 sccm. After the temperature was raised to 600 ° C, argon (100 sccm) and acetylene gas (10 sccm) were introduced, and the carbon deposition was carried out at 600 ° C for 10 minutes, and then the acetylene gas was stopped. It was naturally cooled to room temperature under an argon atmosphere to obtain a one-dimensional carbon-coated SiO x @C1 composite materials.
[0073] Comparative Example 2
[0074] Step 1: Sieving SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13-48μm. x particles.
[0075] Step 2: High temperature carbon deposition: Weigh 5 g of sieved SiO x The particles were ground with 0.5 g of nickel nitrate in an agate mortar and then further mixed in a degassing machine. The mixture was placed in a quartz furnace tube, and then a rotary tube atmosphere furnace was assembled and heated from 600°C to 800°C at a heating rate of 3°C / min under an argon atmosphere with an argon flow rate of 100 sccm. After the temperature was raised to 800°C, argon (100 sccm) and acetylene gas (10 sccm) were introduced, and the carbon deposition was carried out at 800°C for 10 minutes, and then the acetylene gas was stopped. The mixture was naturally cooled to room temperature under an argon atmosphere to obtain a double carbon-coated SiO x @C2 composite materials.
[0076] Comparative Example 3
[0077] Step 1: Sieving SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13-48μm. x particles.
[0078] Step 2: Low temperature carbon deposition: Weigh 5 g of sieved SiO x The particles were placed in a quartz furnace tube, and then a rotary tube atmosphere furnace was assembled and heated to 650°C at a heating rate of 5°C / min in an argon atmosphere with an argon flow rate of 100 sccm. After the temperature reached 650°C, argon (100 sccm) and acetylene gas (10 sccm) were introduced, and the temperature was kept at 650°C for 10 minutes for carbon deposition. Then the acetylene gas was stopped to obtain carbon-coated SiO x @C1 composite materials.
[0079] Comparative Example 4
[0080] Step 1: Sieving SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13-48μm. x particles.
[0081] Step 2: Low temperature carbon deposition: Weigh 5 g of sieved SiO x The sample was placed in a quartz furnace tube and then assembled into a rotary tube atmosphere furnace. The sample was heated to 650°C in an argon atmosphere at a heating rate of 5°C / min and an argon flow rate of 100 sccm. After the temperature reached 650°C, argon (100 sccm) and acetylene (10 sccm) were introduced. The carbon deposition was carried out at 650°C for 10 minutes, after which the acetylene flow was stopped.
[0082] Step 3: High-temperature carbon deposition: The above materials were heated from 650°C to 800°C at a heating rate of 3°C / min in an argon atmosphere with an argon flow rate of 100 sccm. After the temperature reached 800°C, argon (100 sccm) and acetylene (10 sccm) were introduced. The temperature was kept at 800°C for 10 minutes for carbon deposition, and then the acetylene gas was stopped. The material was naturally cooled to room temperature in an argon atmosphere to obtain a double-carbon-coated SiO x @C1@C2 composite material.
[0083] Figure 1 :Silicon oxide SiO x Comparative Example 1: SiO x @C1 and Example 1: SiO x In the XRD pattern of @C1@C2, a broad diffraction peak was detected in the range of 20-25°, which corresponds to amorphous SiO x Phase. For the sample SiO synthesized in Example 1 x @C1@C2, XRD pattern shows a small peak at 2θ=28°, which is derived from silicon (JCPDS No.27-1402), which may be due to SiO x Thermal decomposition reaction occurs at 800℃ to generate Si.
[0084] Figure 2 :(a)Silicon oxide SiO x ; (b) Comparative Example 1: SiO x @C1; (cd) Example 1: SiO x SEM images of @C1@C2. In Figure b, it can be seen that one-dimensional carbon growth occurs at 600℃ and entangles with each other and forms SiO xThe particles are connected to each other to form a cage-like carbon layer. x The one-dimensional carbon on the particles is connected to the particles, which can effectively prevent the aggregation of one-dimensional carbon and ensure the uniformity of component distribution. The conductive network formed by the one-dimensional carbon can improve the conductivity of the material. Figure c shows that during the high-temperature carbon deposition process at 800°C, the surface of the particles is rough, proving that carbon deposition occurs. Figure d shows that there is a small amount of one-dimensional carbon that is not coated with carbon, which proves that there are two types of carbon in Example 1, namely one-dimensional carbon and a dense structure layered amorphous carbon layer.
[0085] Figure 3 :(ab) Comparative Example 2:SiO x @C2 TEM image. x A thick amorphous carbon layer was clearly observed on the particle surface. This indicates that the carbon deposited at 800 °C has amorphous characteristics and the SiO x The bond between particles and carbon layer is tight.
[0086] Figure 4 :(a) Comparative Example 3: SiO x From the SEM image of @C1, it can be seen that the cage-like carbon layer of Comparative Example 1 was not grown when low-temperature carbon deposition was performed without adding a transition metal source; according to (b) Comparative Example 4: SiO x The SEM images of @C1@C2 show that the particle surface is rough, which proves the presence of carbon deposition; combined with Figure c, comparative example 4: SiO x The TEM images of @C1@C2 reveal only one type of carbon, with no distinct lattice fringes, indicating amorphous carbon. This demonstrates that even with both low- and high-temperature stages, only one carbon layer is present during low-temperature carbon deposition without the addition of a transition metal source.
[0087] The materials prepared in Comparative Examples 1-4 and the raw material silicon oxide SiO x Electrode sheets were prepared according to the method described in Example 1 and assembled into a battery.
[0088] Table 1: Raw material SiO at 0.1C current density in the first cycle x Comparative Example 1: SiO x @C1, Comparative Example 2: SiO x @C2, Comparative Example 3: SiO x @C1, Comparative Example 4: SiO x @C1@C2, Example 1: SiO x Electrochemical performance of @C1@C2 materials
[0089]
[0090] As shown in Table 1, in Comparative Examples 1 and 3, no transition metal source is added, and the carbon deposition performance is slightly improved in the low temperature range. Comparative Example 4 and Example 1 show that the addition of a transition metal source can greatly improve the material conductivity and the first-cycle coulombic efficiency.
[0091] Figure 5 :Raw material silicon oxide SiO x Comparative Example 1: SiO x @C1, Comparative Example 2: SiO x @C2, Example 1: SiO x Comparison of the cycling performance of @C1@C2 materials under the conditions of 0.1C in the first cycle and 0.5C in the subsequent cycle. Example 1: SiO x The @C1@C2 material exhibits the best cycling stability and the highest first-cycle Coulombic efficiency (79.89%), indicating reduced side reactions on the electrode surface and the formation of a stable SEI film. This is primarily attributed to the material's synergistically reinforced double carbon layer structure.
[0092] Figure 6 :Raw material silicon oxide SiO x Comparative Example 1: SiO x @C1, Comparative Example 2: SiO x @C2, Example 1: SiO x @C1@C2 material electrochemical impedance spectroscopy. SiO x @C1@C2 samples show the smallest impedance, while SiO x @C1's impedance is also smaller than SiO x @C2. This is because the conductive network formed by C1 improves the SiO x Point and surface contacts between particles. In addition, SiO x @C2's resistance is less than that of the raw material SiO x , indicating that the conductivity of C1 is better than that of C2, and the double carbon layer structure has the best effect in enhancing conductivity.
[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A double carbon-coated SiO x The method for preparing the material is characterized in that: The following steps are involved: (1) mixing silicon oxide and a transition metal source and grinding them to obtain a mixture; (2) subjecting the mixture to low-temperature chemical vapor deposition to achieve carbon coating to obtain a one-dimensional carbon-coated silicon-oxygen material; (3) The one-dimensional carbon-coated silicon-oxygen material is subjected to high-temperature chemical vapor deposition to achieve secondary carbon coating to obtain double carbon-coated SiO x Material.
2. According to claim 1, the double carbon-coated SiO x The method for preparing the material is characterized in that: The transition metal source is ammonium iron oxalate, nickel nitrate, cobalt nitrate or indium nitrate.
3. According to claim 1, the double carbon-coated SiO x The method for preparing the material is characterized in that: The mass ratio of the silicon oxide to the transition metal source is 1:(10-50).
4. The double carbon-coated SiO according to any one of claims 1 to 3 x The method for preparing the material is characterized in that: The atmosphere of the low-temperature chemical vapor deposition and high-temperature chemical vapor deposition in the heating stage is an inert gas, and the atmosphere in the heat preservation stage is a mixed gas including an inert gas and a carbon source gas.
5. According to claim 1, the double carbon-coated SiO x The method for preparing the material is characterized in that: The inert gas is argon or nitrogen; the carbon source gas is acetylene, methane or toluene; the volume flow ratio of the inert gas to the carbon source gas in the mixed gas is 1-10:
1.
6. The double carbon-coated SiO according to claim 1 x The method for preparing the material is characterized in that: The temperature of the insulation stage in the low-temperature chemical vapor deposition is 400-700° C. and the time is 5-30 minutes.
7. The double carbon-coated SiO according to claim 1 x The method for preparing the material is characterized in that: The temperature of the heat preservation stage in the high temperature chemical vapor deposition is 700-900° C. and the time is 5-30 minutes.
8. Double carbon-coated SiO prepared by the method according to any one of claims 1 to 7 x Material.
9. The double carbon coated SiO according to claim 8 x The application of the material in lithium batteries is characterized by: Double carbon coated SiO x The material is used as the active material in the electrode sheet. The electrode sheet is made by coating SiO with double carbon. x The material, the conductive agent and the binder are mixed and coated on the current collector to obtain the product.
10. The double carbon-coated SiO according to claim 1 x The application of the material in lithium batteries is characterized by: The mass ratio of the double carbon-coated silicon oxide material, the conductive agent and the binder is (7-9.3): (0.3-2): (0.4-1); the conductive agent is any one of acetylene black, Ketjen black, conductive graphite or Super P; the binder is any one of styrene-butadiene rubber, sodium carboxymethyl cellulose or polyacrylic acid.
Citation Information
Patent Citations
Double-layer carbon-coated silicon monoxide negative electrode material as well as preparation method and application thereof
CN113363479A